BAHASA PEDAGANG IKAN DI PASAR PANORAMA BENGKULU (KAJIAN SOSIOLINGUISTIK) - Fitriani, Yetri; Rahayu, Ngudining; Wulandari, Catur (Jurnal Ilmiah KORPUS, 2017)
The purpose of this study is to describe the first variantions of language seen in terms of speakers of idiolek, regional origin, gender, and age. The second describes the function of the language used by fish trades in Panorama Bengkulu market. The research uses qualitative descriptive method, with data collection technique, and field note technique. Data analysis techniques in this study include data transcription, data classification, data code, data interpretation, and concluding. The results of this study indicate that the first language of fish traders in Panorama Bengkulu market seen in terms of speakers there idiolek speakers who use the choice of the word “yang” and “mother” as a greeting to buyers who show the characteristic of a speaker, and sosiolek speakers that are the origin of the region that influences the occurrence of variantion language speakers who use Bengkulu Malay, Serawai language in Seluma area, and Serawai language in Bengkulu Selatan area, Lintang language in Empat Lawang area, and the language of Jawa, and the choice of words sentesces, and greetings used speakers show the gender le the male merchant’s expression tends to be brief but clear, in his speech is not a lot of preamble like fish traders who are sex women using speech tend to longand a lot of pleasantries to influence buyers. In terms of age there are traders who are aged 30 and 40 years who use the word necessary and directly to the goal of his conversation sech as “fish mbak” and “thirty five thousand only, want?”. The second there is the language function of the composer which consists of personal functions, interactional functions, instrumental functions, and heuristic functions. In communicating with buyers when buying and selling fish in the Panorama Bengkulu market.